Guinness World Records, 2021 - Glenday, Craig ([London, England] : Guinness World Records Ltd., 2020)
Presents the biggest, smallest, fastest, longest, and other record setters for 2020 in the categories of space, Earth, animals, humans, fantastic feats, science and technology, arts and media, and sports.
Includes index.
Young Adult.
Young Adult
Keywords: Curiosities and wonders; World records; Curiosities and wonders; World records